The Dark Lord Clementine - Horwitz, Sarah Jean (Algonquin Young Readers, 2019)
When her father is cursed by a rival witch, twelve-year-old Clementine Morcerous assumes his duties as Dark Lord of the realm, but soon questions her father's code of good and evil.